Penny Postcard Image of Orange Orchard in Ventura County - United States Post Office::::::
N. W. Blanchard, in partnership with a Santa Barbara nurseryman set out the first orange orchard in 1874. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.